Buzz, buzz, buzz - Barton, Byron (New York : Aladdin Paperbacks, 1995)
A disastrous chain of events in the farmyard begins when the bee stings the bull.
Publisher's Weekly, September 2011
Booklist, July 2010
2.0
K-3
K-3
Publisher's Weekly
Keywords: Animals -- Juvenile fiction; Farm life -- Juvenile fiction; Animals -- Fiction; Farm life -- Fiction; Humorous stories; Animals -- Fiction; Farm life -- Fiction; Humorous fiction